Anti-metastatic and Anticancer Potentials of Synthesized Chalcones in B16-F10 Melanoma Cells Induced Metastatic Lung Cancer in C57BL/6 Mice - Kumar, Nitesh; Kishan, Nunsavath; Biswas, Subhankar; Gourishetti, Karthik; Kamal, Mehnaz; Chamallamudi, Mallikarjuna Rao (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim/Background: Metastasis is the main reason of death in cancer with a key challenge to target it precisely by the available treatments. The current study was designed to assess the anti-metastatic potentials of the synthesized chalcones, Ch-1 and Ch-2. Materials and Methods: In vitro study included cytotoxicity, scratch wound assay and cell cycle analysis of Ch-1 and Ch-2. In vivo study was performed in C57BL/6 mice in a B16-F10 induced metastatic lung cancer model. Results: Ch-1 was found to be a potent cytotoxic agent on cell lines namely, MCF-7 (human breast cancer cells), B16-F10 (melanoma cells), Hela (cervical cancer cells) and HEK (human embryonic kidney cells) with IC50 < 100 µM. Ch-1 deterred the G2/M phase of the MCF-7 cell cycle, S Phase of the HeLa cell cycle and G0-G1 phase of the B16-F10 cell cycle. Scratch wound assay in MCF-7 cells with Ch-1 and Ch-2 showed a significant (p<0.05) prevention in their multiplication when compared to untreated cells at both 24 h and 48 h intervals. In vivo study showed that, oral Ch-1 administration at 100 mg/kg b.w. reduced metastatic lung nodules to 77.32%. Standard drug Quercetin at 100 mg/kg b.w. inhibited the lung tumor nodule formation to 56.5%. However, except for WBC count, Ch-1 (100 mg/kg) also displayed significant improvement in hematological profile. No significant difference was found in any of the groups of animals in mean body weight and major organ weight. Conclusion: Study supports the possible use of Ch-1 as a potential anticancer agent in metastatic lung cancer.
Keywords: Chalcones; Anticancer; B16-F10 melanoma cells; Metastatic lung cancer; Cell Cycle